Mecanismos para problemas de aç\~ao coletiva - Valdir Melo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– Problems of collective action are at the roots of several public policies and, as shown in this text, there are many mechanisms and tools to be used in order to solve those problems. Although three groups of mechanisms and tools have not been stressed in the usual debates of public policy, they make an important contribution: influence on cultural traits (social marketing or public sector marketing), support to morality, and physical configuration of public spaces (design). It is suggested here that they be employed more extensively and with better foundations.
Keywords: H41; Z13; Z18; 330; collective action; social marketing; public sector marketing; morality; design